The Argumentative Indian
India is a large and very diverse country with many distinct pursuits, vastly different convictions, widely divergent customs, and a veritable feast of viewpoints. The Argumentative Indian brings together an illuminating selection of writings from Nobel prize-winning economist Amartya Sen that outline the need to understand contemporary India in the light of its long argumentative tradition. The understanding and use of this rich argumentative tradition are critically important, Sen argues, for the success of India\\\\\\\'s democracy, the defence of its secular politics, the removal of inequalities related to class, caste, gender and community, and the pursuit of sub-continental peace.